Lack of TEK Gene Mutation in Patients with Cutaneomucosal Venous Malformations from the North-Western Region of Algeria. (9th December 2013) - Brahami, Nabila; Aribi, Mourad; Sari, Badr-Eddine; Khau Van Kien, Philippe; Touitou, Isabelle; Lefranc, Gérard; Barat-Houari, Mouna
Abstract : Background . Venous malformations (VM) result from an error in vascular morphogenesis. The first gene suspected in their development is the TEK gene (tyrosine kinase, endothelial). Mutations of this gene have been identified in several Belgian families with a dominant form of the disease. Therefore, we investigated whether mutations in this TEK gene could explain the MV development in patients of families from Tlemcen region (north-western Algeria). Methods . Genomic DNA was extracted from leucocytes of ten patients. The search for mutations in all the 23 exons and in the 5′ and 3′ intronic sequences flanking the TEK gene was performed using PCR amplification and direct sequencing of amplified genomic DNA. Additionally, a search for somatic mutations of the gene TEK was performed on a biopsy of the venous malformation from one of the ten eligible patients. Results . The sequencing of the 23 exons of the TEK gene revealed neither germinal mutation in our ten patients nor somatic mutation in the tissue of the biopsy. Conclusion . The absence of mutation in the TEK gene in the population studied suggests that the TEK gene is not necessarily involved in the onset of VM; its association with these malformations may differ from one population to another.